2015
DOI: 10.1016/j.bej.2015.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of antimicrobial combinations to reduce the use of sodium hypochlorite in the control of planktonic and sessile Escherichia coli

Abstract: Foodborne illness outbreaks linked to fresh produce are becoming more frequent and widespread. The types and properties of the chemical agents used for washing, cleaning and disinfection procedures, particularly their toxicity are the key indicators of environmental performance of a minimally processed vegetables (MPV) industry. The main aims of this work were focused on the evaluation of selected disinfectants (chlorine dioxide, peracetic acid, hydrogen peroxide, copper sulphate, vanillin and sodium bicarbona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…According to previous studies, contaminated hospital surfaces are mostly colonized by monolayer adhered cells with densities of 10 4 -10 6 CFU/cm 2 (values in the range of those found in this study for Escherichia coli and Staphylococcus aureus) (Dancer, 2004;Wren et al 2008;Otter et al 2015). Moreover, it was found that the effects of selected disinfectants were similar on CFU reduction of monolayer adhered cells (2 h adhesion) and biofilms (24 h-old) (Meireles et al 2015).…”
Section: Discussionmentioning
confidence: 90%
“…According to previous studies, contaminated hospital surfaces are mostly colonized by monolayer adhered cells with densities of 10 4 -10 6 CFU/cm 2 (values in the range of those found in this study for Escherichia coli and Staphylococcus aureus) (Dancer, 2004;Wren et al 2008;Otter et al 2015). Moreover, it was found that the effects of selected disinfectants were similar on CFU reduction of monolayer adhered cells (2 h adhesion) and biofilms (24 h-old) (Meireles et al 2015).…”
Section: Discussionmentioning
confidence: 90%
“…Briefly, the 0.1 mL of the culture broth 101 without the microorganism growth was inactivated using 0.9 ml of the inactivation buffer (Lectin 10 g/L, Polyoxyethylene (20) sorbitan monooleate 30 g/L, L-histidine 1 g/L, Tryptone 1 g/L, Na2S2O3˙5H2O 20 g/L) and then inoculated the cells and plated on the TSA plate. The MBCs were determined by the lowest concentration of PAA that completely inhibited the M. psychrotolerans colony growth (Meireles et al, 2015).…”
Section: Evaluation Of Antibacterial Activity Of Paamentioning
confidence: 99%
“…Duarte et al [17] found that the combined ultrasound and dichloroisocyanurate had significantly improved the antibacterial effect. In addition, ultrasound can improve the antibacterial effect of oregano essential oil and organic acids [18,19]. Phenyllactic acid (PLA) has a broad spectrum of effective antibacterial activity against many Gram-positive bacterial species, including S. aureus and Listeria monocytogenes, as well as Gram-negative bacterial species, including S. enteritidis and E. coli.…”
Section: Introductionmentioning
confidence: 99%